Prospects for microbial control in West Africa - Langewald, J.; Cherry, A. (2000)
The prospects for development of microbial control in West Africa are bright, with many stakeholders in plant protection both within and beyond the region becoming increasingly interested. To date however, on the West African market, there are only two microbial products available, and many opportunities remain to be fully explored. Apart from commercially oriented pathways, alternative methods of pathogen propagation and implementation are being studied, to serve the needs of those agricultural sectors which do not provide sufficient profit margins, such as the mainly traditional subsistence systems. Several groups are developing common regional registration frameworks for pesticides, and the need for adapted regulations and guidelines for microbial products is being addressed. This is a strong opportunity for creating a framework which does not only promote commercial products, but also alternative implementation pathways.